A Teachers Role in Addressing Challenges and Strategies in Secondary English Teaching - Putri, Ashifa Nabila; Rachman, Dzul; Sunarti, Sunarti (Borneo Educational Journal (Borju), 2025)
This study explores the multifaceted role of English teachers in addressing the instructional challenges encountered at the secondary school level in Samarinda, Indonesia. Given the increasing demand for English proficiency and the limitations within English as a Foreign Language (EFL) contexts, this research investigates the core obstacles faced by educators and the strategies they implement to enhance student learning outcomes. A qualitative phenomenological approach was employed, using structured interviews with purposively selected English teachers based on experience, educational background, teaching methodology, and school location. Thematic analysis revealed three principal themes: instructional challenges (e.g., time constraints, student apathy, technical limitations), pedagogical considerations in choosing learning strategies, and adaptive solutions such as differentiated instruction and peer collaboration. The findings highlight teachers’ critical role in adjusting instructional methods to students' diverse needs and utilizing collaborative networks to overcome resource limitations. The study contributes original insight by focusing on localized, real-world teacher experiences in a specific urban-rural Indonesian setting an area that remains underrepresented in existing literature. It underscores the necessity of systemic support and continuous professional development for EFL teachers navigating complex classroom dynamics.